2019
DOI: 10.1016/j.nicl.2019.102014
|View full text |Cite
|
Sign up to set email alerts
|

Newborns and preterm infants at term equivalent age: A semi-quantitative assessment of cerebral maturity

Abstract: HighlightsTransient fetal structures are visible on T2 MRI in neonates and can be scored.Radiologically, these structures are different in term and former preterm infants.Maturity of crossroads and subplate particularly discriminates the two groups.Prematurity affects white matter precursors in frontal and occipital areas.At term age, some preterms show accelerated occipital white matter maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 52 publications
(80 reference statements)
4
25
0
Order By: Relevance
“…We also found that the fetal transient compartments (Pittet et al, 2019) have high contrast in the T2w, T1w, FISO, MD, RD and TDI γ c maps.…”
Section: Running Titlesupporting
confidence: 56%
See 3 more Smart Citations
“…We also found that the fetal transient compartments (Pittet et al, 2019) have high contrast in the T2w, T1w, FISO, MD, RD and TDI γ c maps.…”
Section: Running Titlesupporting
confidence: 56%
“…7.B). The parcellation map has 24 regions with the majority being consistent with the transient fetal compartment regions described in the recently introduced extended MRI scoring systems of cerebral maturation (Pittet et al, 2019) including periventricular crossroads, Von Monakow WM segments and subplate. We also identified fast developing regions within the cerebellum and subcortical grey matter.…”
Section: Frontiers 13supporting
confidence: 55%
See 2 more Smart Citations
“…Prematurity also may alter the maturation patter as measured in a study that compared premature and full-terms by equivalent age using 3T MRI T2-weighted and showed that the majority of transient fetal compartments were less mature in preterm group at term equivalent age, though von Monakow segments of the white matter and subplate compartment presented a more advanced maturational stage in the preterm group compared to the term group. 28 These differences are still to be investigated at long term. Because they are the first neural cells to mature, SPNs are the most vulnerable cells to hypoxia-ischemic processes common in prematures.…”
Section: Cognitive Impairmentmentioning
confidence: 98%